Effect of heat treatment on microstructure evolution and strengthening-toughening behavior of high-strength Mg-Gd-Y-Zn-Zr alloy fabricated by wire-arc additive manufacturing - Zihong Wang; Jingfeng Wang; Xin Lin; Le Feng; Lingxiao Ouyang; Chaoneng Dai; Wenzhe Yang; Weidong Huang; Fusheng Pan (Journal of Materials Research and Technology, 2024)
Mg-Gd-Y-Zn-Zr alloy is an important lightweight material in the aerospace field. Wire arc additive manufacturing (WAAM) provides a new route to fabricate large Mg alloy components. Here, a Mg-8Gd-4Y–1Zn-0.5Zr (wt.%) alloy was fabricated using WAAM based on the cold metal transfer (CMT) process. Subsequently, a short-time solid solution + aging treatment was designed to tailor the microstructure. In the as-fabricated condition, the microstructure mainly consisted of fine α-Mg, network (Mg,Zn)3(Gd,Y) eutectic phase, and lamellar γ′ basal precipitate. After 500 °C-1 h short-time solid solution, the eutectic phase rapidly dissolved, the long-period stacking ordered (LPSO) phase formed, and the fine grain was maintained. Due to the good deformation capacity of the fine grains and the kinking deformation capacity of the LPSO phase, the ductility was significantly improved from 5.2 ± 0.4% to 15.5 ± 1.1%. After further 200 °C-64 h artificial aging, dense β′ prismatic precipitates formed. Thanks to the synergistic strengthening of the fine grains and β′ prismatic precipitates, a yield strength of 242 ± 4 MPa was achieved. However, the kinking deformation of the LPSO phase was inhibited, resulting in a drastic decrease of ductility to 6.1 ± 0.5%. Overall, the combination of strength and ductility of the CMT-based WAAM-processed Mg-Gd-Y-Zn-Zr alloy under an optimized heat treatment regime can be superior to those of the cast Mg-Gd-Y-Zn-Zr alloys with similar contents of Gd and Y elements. This work can guide further performance optimization for WAAM-processed Mg-Gd-Y-Zn-Zr alloys.